Experimental investigation and analytical prediction on bond behaviour of CFRP-to-concrete interface with FRP anchors - Kun Dong; Yu Gao; Shutong Yang; Zhisong Yang; Jitong Jiang (Case Studies in Construction Materials, 2023)
Hybrid bonded technology with fiber-reinforced polymer (FRP) anchors can effectively improve the load capacity of carbon fiber-reinforced polymer (CFRP)-to-concrete interface. To investigate the reinforcement effect of FRP anchors, tensile shear tests of seventeen CFRP-concrete bonded joints with additional FRP anchors were conducted in this paper. The effects of the construction sequence, anchor position, and type of FRP anchor were considered in the experimental investigation. It was found that bonding CFRP sheet before installing FRP anchor and construction simultaneously could ensure the integrity of FRP anchor and provide a better anchor effect. The ultimate load-carrying capacity was increased with the increasing of plate length after anchor, that is the effect of anchor position. From the results of specimens with different types of FRP anchors at the same location, the FRP anchor composed of multiple small anchors can take effect earlier. By fitting the test results, the exponential bond-slip model for the CFRP-to-concrete interface and the elastic constitutive model for the FRP anchor were obtained. Further, substituting the two constitutive models, analytic theoretical models for load-slip curves and strain distribution were derived to predict the bond behavior of FRP anchored CFRP-to-concrete interface in this paper. The comparison between the prediction results and experimental data shows the good predictive accuracy of these analytical models.